2015
DOI: 10.1103/physrevb.91.205311
|View full text |Cite
|
Sign up to set email alerts
|

Temperature-driven transition from a semiconductor to a topological insulator

Abstract: We report on a temperature-induced transition from a conventional semiconductor to a two-dimensional topological insulator investigated by means of magnetotransport experiments on HgTe/CdTe quantum well structures. At low temperatures, we are in the regime of the quantum spin Hall effect and observe an ambipolar quantized Hall resistance by tuning the Fermi energy through the bulk band gap. At room temperature, we find electron and hole conduction that can be described by a classical two-carrier model. Above t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
36
0
6

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(43 citation statements)
references
References 25 publications
1
36
0
6
Order By: Relevance
“…Large positive (and often linear) MR was reported in graphene and topological insulators close to charge neutrality [14][15][16][17][18][19][20][21][22] [36][37][38][39] that this effect could be a direct condensed matter manifestation of the Adler-Bell-Jackiw chiral anomaly [40][41][42] . However, the unexpected variety of materials exhibiting negative MR [8][9][10][11][31][32][33][34][35] does not support the idea that such measurements may provide a "smoking gun" for detecting a Weyl semimetal 37,39 .…”
mentioning
confidence: 99%
“…Large positive (and often linear) MR was reported in graphene and topological insulators close to charge neutrality [14][15][16][17][18][19][20][21][22] [36][37][38][39] that this effect could be a direct condensed matter manifestation of the Adler-Bell-Jackiw chiral anomaly [40][41][42] . However, the unexpected variety of materials exhibiting negative MR [8][9][10][11][31][32][33][34][35] does not support the idea that such measurements may provide a "smoking gun" for detecting a Weyl semimetal 37,39 .…”
mentioning
confidence: 99%
“…14 It has been recently demonstrated that a transition between BI and TI phases can be driven either by electric field 15,16 , applied along the growth direction, or by temperature 17,18 . However, the mentioned works were focused on the evolution of the band structure due to transition between BI and TI phases only, while temperature and electric field effects in the SM phase were ignored.…”
mentioning
confidence: 99%
“…Последнее открывает допол-нительные возможности для создания перспективных " топологических" приборов, работающих с использова-нием краевых каналов проводимости [19]. К настоящему времени теоретически рассматривались возможности осуществления фазового перехода в КЯ HgTe/CdHgTe между состояниями тривиального и топологического изоляторов с помощью внешнего электрического по-ля [20,21], температуры [10,21,22] и давления [22]. Экс-периментально качественное изменение зонного спектра и наличие такого перехода при изменении темпера-туры впервые было продемонстрировано с помощью транспортных [10] и магнитооптических измерений [23].…”
Section: международный симпозиум "unclassified
“…5 и 6 вид зависимостей энер-гетического зазора между валентной зоной и зоной проводимости в точке k = 0 принципиально отличается для структур с нормальным и инвертированным зонным спектром. Как показано в работах [10,22], основное влияние температура оказывает на положение подзоны E1 -с ростом температуры энергия подзоны в точке k = 0 увеличивается. В образцах с нормальным зонным спектром это просто приводит к увеличению ширины запрещенной зоны.…”
Section: международный симпозиум "unclassified
See 1 more Smart Citation